Diseño y Construcción de un Sistema para Moldeo de Plástico Reciclado de la Vereda Cerro Rico (2023)
Solid waste management is a logistic and environmental problem, that affects in high proportion some smalltown and places where there is no collection or treatment waste service. This is the case of Cerro Rico smalltown, which does not have collection waste service, sanitary landfill or other waste management alternative. Antonio Nariño University campus Buga, though social work service, met this case and began a project about plastic recycling, offering to the community small talks about correct plastic classification in order to help the environment.